"Development And Assessment of Immediate Release Nitrofurantoin Tablet and Sustained Release Trimethoprim Tablet: Formulation, Characterization and Comparative Evaluation" - Kute, Vaibhav Ghansham; Singh, Manmeet (International Journal of Membrane Science and Technology, 2023)
The research includes an examination of material properties, an investigation into the compatibility of the drug and excipients, the development of analytical techniques, and the determination of tablet production methods for immediate and sustained release layers. The methodology for material characterization encompassed the analysis of the pharmaceuticals’ solubility in various aqueous solutions and buffers. The evaluation of the compatibility between excipients and medications was conducted utilizing FT-IR spectroscopy. Furthermore, calibration curves were devised by the research team for Nitrofurantoin and Trimethoprim, enabling the quantification of these pharmaceutical substances via UV spectrophotometry. The preparation of the tablets involved the utilization of direct compression and moist granulation methods, respectively, for the immediate and sustained release layers. This required the application of a variety of excipients and polymers. The tablets underwent a thorough evaluation in a controlled laboratory environment, which encompassed assessments of their dimensions, resistance to deformation, mass variability, and susceptibility to fracturing, concentration of active component, breakdown time, and solubility. The findings demonstrated that the regression coefficients in the calibration curves were substantial, thereby validating the accuracy of the drug concentration estimations. The results of the solubility studies indicate that Nitrofurantoin becomes more soluble in acidic environments. However, it should be noted that the solubility of both Trimethoprim and Nitrofurantoin is influenced by various solvents and buffers. An investigation into the compatibility of pharmaceuticals and the excipients was conducted through the utilization of FT-IR spectroscopy to ascertain such compatibility or interaction. A micromeritics analysis of granule flow parameters unveiled batch-specific variations in flow characteristics which will impact the manufacturing procedure. Upon scrutinizing the tablets, discrepancies in multiple measurements were discovered among various samples, suggesting the possibility of atypical tablet characteristics. Nitrofurantoin and Trimethoprim exhibited a progressive release from their tablets over time in various samples, as indicated by the drug release profiles observed in vitro; this suggests that the tablets have distinct release kinetics. Nevertheless, the medication release data exhibited irregularities in its presentation, such as sporadic inputs, absent values, and potentially erroneous statistics. The presence of these inconsistencies has the potential to compromise the dependability and comprehension of the results. In brief, the research provides extensive knowledge regarding the development, examination, and assessment of Nitrofurantoin rapid release tablets and Trimethoprim sustained release tablets.